(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Children constitute a highly vulnerable population subgroup due to ongoing physiological development, immature detoxification mechanisms, and comparatively higher food consumption per unit of body mass. The present study aims to perform a comprehensive hygienic evaluation of potential health risks to children arising from the dietary intake of vegetables containing residual levels of pesticides. The assessment is based on analytical determination of pesticide residues in widely consumed vegetable commodities using validated chromatographic techniques, followed by exposure modeling incorporating age-specific consumption patterns and body weight parameters. Non-carcinogenic health risks were characterized through the calculation of hazard quotients and hazard indices in accordance with internationally recognized risk assessment frameworks. The obtained results demonstrated the presence of multiple pesticide residues in vegetable samples, and although the majority of detected concentrations complied with established maximum residue limits, cumulative and chronic exposure scenarios revealed an elevated contribution to overall risk, particularly among younger age groups. These findings indicate that regulatory compliance with residue limits does not necessarily preclude potential health concerns for children and underscore the necessity for refined hygienic monitoring, cumulative risk assessment approaches, and the implementation of preventive strategies aimed at minimizing dietary pesticide exposure in pediatric populations.